ANALISA PEMBANGUNAN PARTISIPATIF DALAM MUSRENBANG-DES TAHUN 2017 DI GAMPONG PANGGONG KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Fadhil Ilhamsyah; Jumpa Parningotan Purba (Jurnal Public Policy, 2018)
This research aims to find out how the implementation of participatory development and to know the factors that affect public participation Gampong Panggong subdistrict of West Aceh Regency Hero Johan. Methods used in this research is descriptive qualitative method where data is taken from interviews, field notes, documents, memos and other documents to get the proper interpretation. The results showed that overall the participatory development implemetasi in Gampong Panggong subdistrict of Aceh Heroes Baratmasih Johan less good, in this case only a part of the community that are involved in the planning development. This is due to social and economic factors which the community at large as a fisherman so just focus on the fulfillment of survival. In addition the implementation of planning construction of Gampong Panggong subdistrict of West Aceh Regency Hero Johan. dietemukannya multiple factors that affect the level of public participation in the planning of development in Gampong Panggong is the factor endowments include presence awareness, public participation, and support from the Government and society. While restricting factors include poor quality of education, low income levels, limited employment and diperdesaan.Keywords: Implemetasi, Participatory development